Reducing meat consumption: the case for social marketing - Bogueva, D.; Marinova, Dora; Raphaely, T. (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to explore reasons behind meat consumption. It aims to find out what motivates meat consumers and explore the opportunities of social marketing to counteract negative environmental and health trends. Design/methodology/approach: An exploratory Australian survey of Sydney consumer red meat choices is used covering dietary preferences, meat eating patterns, reasons and levels of concern for economic and environmental issues. Analysis of dietary guidelines and marketing campaigns in relation to the survey findings is conducted. Findings: The survey highlights: lack of awareness about the link between meat consumption and environmental well-being; widespread inaccuracy of health messages related to meat consumption; influence of the meat industry in promoting excessive meat consumption; pervasiveness of the link between red meat consumption and national identity, social status, prestige and masculinity; and urgent need for government-supported social marketing interventions and the demarketing of meat. Originality/value: This is the first study to propose social marketing based on the health and environmental co-benefits of reduced red meat consumption.